Exploring the relationship of ESG score and firm value using fsQCA method: Cases of the Chinese manufacturing enterprises - Zhong, Shen; Hou, Junzhu; Li, Junwei; Gao, Wei (Frontiers in Psychology, 2022)
The basic purpose of a business is to maximize value. With the increased expectations for companies’ social responsibility practices and sustainability, sustainability management has become a must for many companies to maximize value in the current competitive environment. Environmental, social and governance (ESG) are widely used indicators to evaluate corporate social responsibility performance. However, there is a lack of combined view on the three dimensions. This study aims to explore the sources of corporate value from the sustainability perspective. By using fsQCA (fuzzy-set qualitative comparative analysis), we proposes a configurational model consisting of environmental, social, governance, size and profitability to investigate the value-enhancing mechanisms of corporate social responsibility. The study shows that high enterprise value can be achieved through multiple paths, which can be categorized as resource-constrained type, slack resources type and good management type.